Konsepsi Gratifikasi sebagai Korupsi bagi Pejabat Publik - Irvan Sebastian Iskandar (Jurnal Administrasi Publik, 2023)
Gratification is an act that is as dangerous as bribery, however, this act is still tolerated in the social life of Indonesian society in general. Data compiled from the Corruption Eradication Commission shows that the number of gratification reports in total value has continued to increase over the past five years. During this time, many public officials have not escaped criminal charges and fines for accepting them. Unlike bribery, this act is carried out at the end when the service has been completed without prior agreement on the value of the material given. As its gray area, gratuities are used as a means of maintaining and obtaining a social relationship, access, and fostering good networks when living in society. By using a qualitative method through a literature review, this research tries to explain gratuity as an act of corruption, the difference between gratuities that are considered bribes and those that are not considered bribes. The results are, first, that gratuities do indeed fall into a form of cheating in the type of corruption acts. Second, there is a difference between gratuities and bribes, although some gratuities can be considered bribes and some are not considered bribes.